2011
DOI: 10.1179/crn.2011.032
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Joint Disk Fracture: A Case Report

Abstract: A case of a patient with a fracture of the temporomandibular joint (TMJ) disk is reported. The patient presented with posterior bilateral open-bite and difficulty to chew due to lack of contact between the posterior teeth. Diagnosis of disk fracture of the right TMJ was made based on magnetic resonance imaging (MRI), with posterior displacement of the posterior fragment of the disk, causing the posterior open-bite, and anterior displacement of the anterior fragment of the disk. TMJ manipulation failed to repos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
6
0
2
Order By: Relevance
“…Considerable joint effusion was also observed on MRI in the present two cases, a finding that was also reported by Melis et al 11 It has been suggested that joint effusion represents an inflammatory response; 26,27 therefore, these findings suggest a possible relationship between disc fracture and inflammation. Morphological change can also be contributed by the inflammatory cascade, leading to subsequent degenerative changes in the TMJ, such as increased surface roughness, depleted lubricant and, ultimately, increased friction.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Considerable joint effusion was also observed on MRI in the present two cases, a finding that was also reported by Melis et al 11 It has been suggested that joint effusion represents an inflammatory response; 26,27 therefore, these findings suggest a possible relationship between disc fracture and inflammation. Morphological change can also be contributed by the inflammatory cascade, leading to subsequent degenerative changes in the TMJ, such as increased surface roughness, depleted lubricant and, ultimately, increased friction.…”
Section: Discussionsupporting
confidence: 74%
“…When the articular surface is roughened by degenerative changes in the condylar head, the disc may be much more prone to abrasion even during routine activities owing to the increased friction between the disc and bony structures of the TMJ, such as the glenoid fossa and condyle. 25 Considering the lack of trauma history and the pronounced occlusal attrition in the present two cases, we suspect that the hypothesis of Melis et al 11 is the aetiology, that is, microtrauma may have triggered the disc fractures by causing mechanical damage to the intermediate portion of the TMJ disc.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations